Constructing a measure of the meaning of life among kindergarten children at the age of (5-6) years (Journal of the College of Basic Education, 2022)
Adler asserts in his book Mening of life that children realize at very early stages of their lives the meaning of life that has begun to form. At the end of the fifth year of a child's life, it becomes clear that a specific pattern of behavior has developed and crystallized. We can even recognize the existence of an independent way of dealing with the problems and situations facing that child, and we can call this independent way of dealing with problems a name